Iso-Oncotic Albumin Mitigates Brain and Kidney Injury in Experimental Focal Ischemic Stroke - Mendes, Renata de S.; Martins, Gloria; Oliveira, Milena V.; Rocha, Nazareth N.; Cruz, Fernanda F.; Antunes, Mariana A.; Abreu, Soraia C.; Silva, Adriana L.; Takiya, Christina; Pimentel-Coelho, Pedro M.; Robba, Chiara; Mendez-Otero, Rosália; et al. (Frontiers in Neurology, 2020)
Background: There is widespread debate regarding the use of albumin in ischemic stroke. We tested the hypothesis that an iso-oncotic solution of albumin (5%), administered earlier after acute ischemic stroke (3 hours), could provide neuroprotection without causing kidney damage, compared to a hyper-oncotic albumin (20%) and saline. Objective: To compare the effects of saline, iso-oncotic albumin, and hyper-oncotic albumin, all titrated to similar hemodynamic targets, on the brain and kidney. Methods: Ischemic stroke was induced in anesthetized male Wistar rats (n=30; weight 437±68g) by thermocoagulation of pial blood vessels of the primary somatosensory, motor, and sensorimotor cortices. After 3 hours, animals were anesthetized and randomly assigned (n=8) to receive 0.9% NaCl (Saline), iso-oncotic albumin (5% ALB), and hyper-oncotic albumin (20% ALB), aiming to maintain hemodynamic stability (defined as distensibility index of inferior vena cava <25%, mean arterial pressure >80 mmHg). Rats were then ventilated using protective strategies for 2 hours. Of these 30 animals, 6 were used as controls (focal ischemic stroke/no fluid). Results: The total fluid volume infused was higher in the Saline group than in the 5% ALB and 20% ALB groups (meanSD, 4.31.6 vs. 2.70.6 and 2.60.5 mL, p=0.03 and p=0.02, respectively). The total albumin volume infused (g/kg) was higher in the 20% ALB group than in the 5% ALB group (1.4±0.6 vs. 0.4±0.2, p<0.001). Saline increased neurodegeneration (Fluoro-Jade C staining), brain inflammation in the penumbra (higher tumor necrosis factor-alpha expression), and blood-brain barrier damage (lower gene expressions of claudin-1 and zona occludens-1) compared to both iso-oncotic and hyper-oncotic albumins, whereas it reduced the expression of brain-derived neurotrophic factor (a marker of neuroregeneration) compared only to iso-oncotic albumin. In the kidney, hyper-oncotic albumin led to greater damage as well as higher gene expressions of kidney injury molecule-1 and interleukin-6 than 5% ALB (p<0.001). Conclusions: In this model of focal ischemic stroke, only iso-oncotic albumin had a protective effect against brain and kidney damage. Fluid therapy thus requires careful analysis of impact not only on the brain but also on the kidney.